Influence of "terroir" factors and vineyard management (organic, biodynamic) on plant performance and fruit quality of grapevines - Döring, Johanna; Justus Liebig University Giessen (My University, 2018)
Plant performance and fruit quality of grapevines are influenced by a wide range of terroir factors. These factors, namely climate, soil as well as agricultural practices often called the human factor in terroir all determine final wine quality to a high extend. Agricultural management is an important tool to adapt agricultural systems to specific environmental conditions. By comparing different management systems several parameters are usually varied together among treatments, such as soil management, fertilization strategy, pest and disease management, application of compost and crop rotations of annual cropping systems. The most wide-spread viticultural management systems today are integrated, organic and biodynamic viticulture, even though organic and biodynamic viticulture are gaining more and more importance and attention among consumers and producers in the last decades. The aim of this thesis was to establish a method for fast and accurate LAI measurements in the vineyard on one hand and to describe the influence of terroir factors and vineyard management systems on plant performance and fruit quality of grapevines on the other hand by assessing vine water status, physiological activity, standard agronomical parameters as well as LAI. A reliable, fast and accurate method to non-destructively and dynamically assess leaf area was established which can be applied in a small scale in the field. Different protocols for indirect estimation of leaf area index (LAI) by gap fraction analysis in VSP trained grapevines (Vitis vinifera L. cv. Riesling) were tested and correlated to direct leaf area measurements. LAI measurements were carried out using the portable Plant Canopy Analyzer (PCA, LAI-2200, LI-COR, Lincoln, NE, USA). One optimized protocol was chosen, the calibration equation was determined and the protocol was successfully used in the field trial in Geisenheim, Germany, comparing integrated, organic and biodynamic viticulture to assess LAI throughout the growing season as well as for determining leaf area to fruit weight-ratio at harvest.Within the second approach of this doctoral dissertation the influence of the terroir factors soil water-holding capacity and grapevine genotype on plant performance was assessed. For this purpose a greenhouse trial was set up comparing the physiological behavior of two grapevine genotypes (Cabernet Sauvignon and Syrah, near-isohydric and near-anisohydric) on two different soil substrates differing in their capacity to withhold water (water-draining and water-retaining). Stem-water potentials together with stomatal conductance and embolism formation (percent loss of conductivity PLC) were determined to describe physiological response mechanisms of the two different grapevine genotypes on two soil substrates. Considering the different characteristic traits of the two grapevine genotypes and the two types of substrate in relation to soil water potential it can be deduced that there are optimal set-ups of combinations of genotype and water-holding capacity, but interactions between genotype and substrate did not occur. Syrah might have more specific requirements concerning the environmental conditions under which it shows optimal growth. Cabernet Sauvignon, in contrast, might be more universally usable compared to Syrah due to its characteristic near-isohydric behavior under drought. Yet all these observations need further confirmation and approval, since the number of plants included in the trial was low and thus influence of environmental factors in the greenhouse could not be excluded to a satisfactory extent. The main objective of the third study included in the current doctoral dissertation was to determine growth, yield and fruit quality of grapevines under organic and biodynamic management in relation to integrated viticultural practices. Moreover, the mechanisms for the observed changes in growth, yield and fruit quality should be investigated by determining nutrient status, physiological performance of the plants and disease incidence on bunches in three consecutive growing seasons. A field trial (Vitis vinifera L. cv. Riesling) was set up at Hochschule Geisenheim University, Germany, in 2006. The integrated treatment was managed according to the code of good practice. Organic and biodynamic plots were managed according to Regulation (EC) No 834/2007 and Regulation (EC) No 889/2008 and according to ECOVIN- and Demeter-Standards, respectively. Due to the investigation of important parameters that induce changes especially in growth and yield of grapevines under organic and biodynamic management the study can potentially provide guidance for defining more effective farming systems.For a broader evaluation of the effects of organic and biodynamic viticulture compared to integrated or conventional viticulture a review of currently available literature was included into the doctoral dissertation. Effects of conventional, organic and biodynamic viticulture on soil properties, biodiversity, vine growth and yield, disease incidence, grape composition, sensory characteristics and wine quality were assessed and summarized. Only studies with representative field replicates or studies with a representative number of samples were included into the review. Yet studies were partially heterogenic and limited in number and publication bias cannot be excluded. In order to predict the behavior of vines under organic and biodynamic viticulture in different terroirs worldwide parameters mediating between terroir and plant performance and thus fruit quality such as physiological activity and PLC could eventually be used. This would provide the possibility to further adapt the practices of organic and biodynamic viticulture to environmental conditions worldwide.

Das Pflanzenwachstum und die Fruchtqualität landwirtschaftlicher Nutzpflanzen wird von einer Vielzahl an sogenannten Terroir-Faktoren beeinflusst. Die Bewirtschaftung einer landwirtschaftlichen Fläche ist ein bedeutendes Instrument zur Anpassung landwirtschaftlicher Systeme an bestimmte Umweltfaktoren. Beim Vergleich verschiedener landwirtschaftlicher Bewirtschaftungssysteme werden üblicherweise verschiedene Parameter zusammen variiert, wie z.B. Bodenpflege, Düngung, Pflanzenschutzstrategie, Kompostgabe und Fruchtfolge einjähriger Kulturen. Die heute am meisten verbreiteten weinbaulichen Bewirtschaftungssysteme sind der integrierte, ökologische und biodynamische Anbau, wobei ökologischer und biodynamischer Weinbau in den letzten zwei Dekaden bei Konsumenten sowie bei Produzenten mehr und mehr an Bedeutung und Aufmerksamkeit gewinnen. Das Ziel dieser Doktorarbeit war einerseits die Etablierung einer schnellen und zuverlässigen Methode der LAI-Messung im Weinberg und andererseits die Beschreibung des Einflusses von Terroir-Faktoren und weinbaulicher Bewirtschaftung (ökologisch, biodynamisch) auf das Pflanzenwachstum und die Fruchtqualität der Rebe mittels Bestimmung des Wasserhaushalts der Reben, der physiologischen Aktivität, des LAI und weiterer pflanzenbaulicher Kenngrößen. Eine robuste, schnelle und genaue Methode zur nicht-destruktiven und dynamischen Erfassung der Blattfläche in kleinen Weinbergsparzellen wurde etabliert. Dazu wurden verschiedene Messprotokolle zur indirekten Schätzung des Blattflächenindex (LAI) mittels gap fraction analysis in einem Weinberg mit Spaliererziehung (Vitis vinifera L. cv. Riesling) getestet und mit direkten, destruktiven Blattflächenmessungen korreliert. Die LAI-Messungen wurden mit dem tragbaren Plant Canopy Analyzer (PCA, LAI-2200, LI-COR, Lincoln, NE, USA) durchgeführt. Eines der Protokolle wurde ausgewählt, optimiert, kalibriert und eingesetzt. Im zweiten Teil der vorliegenden Arbeit wurde der Einfluss der Terroir-Faktoren Wasserhaltefähigkeit des Bodens und Rebsorte auf das Pflanzenwachstum bestimmt. Dazu wurde die physiologische Aktivität zweier Rebsorten (Cabernet Sauvignon und Syrah, iso- bzw. anisohydrisch) auf zwei unterschiedlichen Bodensubstraten, die sich in ihrer Wasserhaltefähigkeit unterschieden, im Gewächshaus verglichen mittels Stammwasserpotenzial, stomatäre Leitfähigkeit und Emboliebildung im Xylem (percent loss of conductivity PLC). Betrachtet man die unterschiedlichen Verhaltensweisen der zwei Rebsorten auf den beiden untersuchten Bodensubstraten je nach Bodenwasserpotenzial, kann man davon ausgehen, dass es optimale Kombinationen aus Rebsorte und Bodensubstrat für die einzelnen Bodenwasserpotenzialniveaus gibt. Jedoch traten keine Wechselwirkungen zwischen Rebsorte und Bodensubstrat auf. All diese Erkenntnisse bedürfen jedoch einer wissenschaftlichen Bestätigung, da die Anzahl von Reben im Versuch gering war und ein Einfluss der Umweltfaktoren im Gewächshaus nicht ausgeschlossen werden kann. Die Bestimmung von Wachstum, Ertrag und Traubenqualität der Reben unter ökologischer und biodynamischer Bewirtschaftung im Vergleich zur integrierten Wirtschaftsweise war das Hauptziel der dritten Publikation. Außerdem sollten die Ursachen der Unterschiede in Wachstum, Ertrag und Traubenqualität zwischen den Bewirtschaftungssystemen beschrieben werden. Dazu wurde der Nährstoffhaushalt der Reben, die physiologische Aktivität sowie die Befallshäufigkeit und -stärke der wichtigsten Pilzkrankheiten der Rebe in drei aufeinander folgenden Versuchsjahren betrachtet. An der Hochschule Geisenheim wurde dazu in 2006 ein Feldversuch (Vitis vinifera L. cv. Riesling) etabliert. Die integrierte Variante wurde nach guter fachlicher Praxis bewirtschaftet. Die ökologische und biodynamische Bewirtschaftung erfolgte nach VO (EC) No 834/2007 und VO (EC) No 889/2008 und ECOVIN- bzw. Demeter-Standards. Die Beschreibung der Ursachen für die Unterschiede in Wachstum und Ertrag zwischen integrierter Bewirtschaftung einerseits und ökologischer und biodynamischer Bewirtschaftung andererseits kann dazu beitragen, Handlungsempfehlungen für die einzelnen Bewirtschaftungsformen zu entwickeln und die Effektivität der jeweiligen Bewirtschaftungssysteme zu steuern.Für eine umfassendere Bewertung der Effekte ökologischer und biodynamischer Bewirtschaftung im Weinbau wurde ein Review der derzeit vorhandenen Studien in die vorliegende Dissertation integriert. Effekte der konventionellen, ökologischen und biodynamischen Bewirtschaftung im Weinbau auf Bodenparameter, Biodiversität, Rebenwachstum, Ertrag, Schaderregerbefall, Traubenqualität, Weinqualität und sensorische Eigenschaften der Weine wurden bestimmt und zusammengefasst. Lediglich Studien mit repräsentativen Feldwiederholungen oder Studien mit einer repräsentativen Anzahl an Proben wurden in das Review einbezogen. m Wachstums- und Ertragseigenschaften der Reben unter ökologischer und biodynamischer Bewirtschaftung unter unterschiedlichsten Umweltbedingungen vorhersagen zu können, erscheint es plausibel, Messgrößen heranzuziehen, die eine Vermittlerrolle zwischen Terroir und Pflanzenwachstum bzw. Fruchtqualität einnehmen, wie z.B. physiologische Aktivität und Emboliebildung im Xylem. Dadurch bestünde die Möglichkeit, die Praktiken des ökologischen und biodynamischen Weinbaus weiter an die Umweltgegebenheiten der unterschiedlichsten Terroirs weltweit anzupassen.
Einfluss von Terroir-Faktoren und Bewirtschaftungssystem (ökologisch, biodynamisch) auf das Pflanzenwachstum und die Fruchtqualität bei Reben
Keywords: Weinbau; Rebe; Terroir; ökologisch; biodynamisch; viticulture; grapevines; terroir; organic; biodynamic; ddc:630